Penyediaan Layanan Berkesehatan Di Bus Trans Semarang dan Haltenya berdasarkan Pendapat Penumpang - Berlian, Ismulia Nur; Manullang, Okto Risdianto (Teknik PWK (Perencanaan Wilayah Kota), 2024)
BLU UPTD Trans Semarang as a provider of public transportation services in the city of Semarang tries to create secure, safe and healthy public transportation by providing health facilities at buses and Trans Semarang bus stops. This study aims to analyze the conditions and needs of health facilities on Trans Semarang buses and their stops based on passenger opinions in an effort to provide health services on Trans Semarang buses and their bus stops during the pandemic and post-pandemic. This study uses a quantitative descriptive analysis to describe the characteristics of passengers who still use Trans Semarang during the pandemic, the condition of health facilities, and the need for health facilities. The condition of the health facilities at the Trans Semarang bus and its bus stop is good with a score of 69%-84%, except for the ventilation health facility at the bus stop which gets a score of 88% that inculde to the very good category and the temperature check facility at the Trans Semarang bus stop which gets a score of 57 % that include to the sufficient category. From that condition, passengers prioritize three health facilities on the bus, those are cleaning equipment (score 83.90%), PPE for employees (score 82.30%), and social distancing signs (score 72.86%). While at the bus stop, the priority needs for health facilities are PPE for employees (score 82.96%), cleaning equipment (81.92%), and social distancing signs (score 77.02%). Regarding the sustainability of providing health facilities after the pandemic, 91% of Trans Semarang passengers and the BLU UPTD Trans Semarang agreed to continue implementing it until after the pandemic to prevent the transmission of other diseases at Trans Semarang buses and bus stops.